LCC112: English for Communicative Competence II - UiTM, Academy of Language Studies (2023)
This course is designed to build students’ receptive, productive, interactive and language competence skills to help students improve their proficiency from CEFR B1 (high) level to the CEFR B2 (low) level in order to perform effectively and competently in the social and academic contexts. This is done through the integration of the language skills (listening, reading, speaking, writing). This course aims to develop the communicative language strategies: reception, production, interaction and mediation skills in the personal domains.